Nestor Pilyavsky’s "Western Liao": mythology and imagery of space - B. E. Nosenok, (Ukrainian Cultural Studies, 2018)
This article is an attempt to prepare an image. But this time the image falls not into a plot (like a storyline) and composition, but into time and space. It has been repeatedly noted (especially it is subject to literary criticism) that the image (in this case an artistic image) builds its own space-time grid of coordinates, and therefore time and space can gallantly violate the laws of physics here. Also, one of the main obvious goals of this culturological investigation is a comparison of the methods and techniques of poetry and prose, a hand hold of the specifics of time’s and space’s expression in verse and novelistics. This goal is realized by referring to the oeuvre of Nestor Pilyavsky. Nestor is a Russian writer and an author of the book "Western Liao". This work simultaneously demonstrates a phenomenon that can be called a mythologization of space, and also the structure of the book is distinguished by a combination of poetic components and prose narratives. In addition, the same theme slips in the reflections of the last great French novelist – Marcel Proust, who emphasizes the differences in the representation of the world that is performed by a poet or a novelist, concordantly. However, if Marcel Proust in the work “In Search of Lost Time" (as can be seen from the title of this epic work) was looking for time, then Nestor Pilyavsky in his book "Western Liao" is looking for space. He wants to return to some past, perhaps he wants to go home (and the name "Nestor" means "whoever that comes home"). Space-time problems erase the boundaries between conventional linear division into the past, the present and the future. It can be seen that a creative work destroys this separation, the destruction of which is revealed most clearly in modern decadent movements. Decadence is a characteristic feature of any transitional, intermediate period when the balance of life is violated and when it is difficult to draw a dividing line between genius, brilliance, and insanity. Decadence is a period of time and a point in space when it is difficult to distinguish dreams and reality from each other. Nestor Pilyavsky calls himself a decadent not without good reason. But modernity, which turns out to be the destruction of the habitual norms of life, is often drawn by the emptiness of the imagination by nothing more than a new, cyclical decadence, and "Western Liao" is an excellent attempt to invent a new, suitable space.
Keywords: image, time, spatiality, space mythology, decadence, poetry, prose